2013
DOI: 10.3389/fphys.2013.00248
|View full text |Cite
|
Sign up to set email alerts
|

It's not black or white—on the range of vision and echolocation in echolocating bats

Abstract: Around 1000 species of bats in the world use echolocation to navigate, orient, and detect insect prey. Many of these bats emerge from their roost at dusk and start foraging when there is still light available. It is however unclear in what way and to which extent navigation, or even prey detection in these bats is aided by vision. Here we compare the echolocation and visual detection ranges of two such species of bats which rely on different foraging strategies (Rhinopoma microphyllum and Pipistrellus kuhlii).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(87 citation statements)
references
References 71 publications
(85 reference statements)
3
82
0
Order By: Relevance
“…Bats rely on vision for long-distance orientation (23)(24)(25), are known or suspected to orient through landscapes using light cues, such as stars and postsunset glow (26,27), and use visual cues to help them find roosts in trees (28). The effects of moonlight on bat activity and fatality at turbines are not well understood, but a study in Alberta, Canada, reported higher fatality rates of silver-haired bats (Lasionycteris noctivagans) at wind turbines on nights when the moon was fully illuminated (29).…”
Section: Discussionmentioning
confidence: 99%
“…Bats rely on vision for long-distance orientation (23)(24)(25), are known or suspected to orient through landscapes using light cues, such as stars and postsunset glow (26,27), and use visual cues to help them find roosts in trees (28). The effects of moonlight on bat activity and fatality at turbines are not well understood, but a study in Alberta, Canada, reported higher fatality rates of silver-haired bats (Lasionycteris noctivagans) at wind turbines on nights when the moon was fully illuminated (29).…”
Section: Discussionmentioning
confidence: 99%
“…Some echolocating bats use vision to complement auditory information when hunting (Eklöf and Jones 2003) and, if vision and echolocation provide conflicting information, visual information is used in preference (Orbach and Fenton 2010). Vision can also be more effective than echolocation over long distances (Boonman et al 2013), and the California leaf-nosed bat Macrotus californicus relies more on vision when hunting prey under low levels of illumination equivalent to a moonlit night (Bell 1985).…”
Section: Bat Visionmentioning
confidence: 99%
“…By plugging in the estimated emission intensity for this species (P t ¼ 135 dB SPL [18]) and the estimated minimum intensity detectable by our microphone, a detection range of ca 20 m is reached (when solving the equation numerically with Matlab). The microphone's P r -the minimal detectable intensity (or the internal noise floor) of our microphone-was estimated by analysing the internal noise of the microphone by comparison with a calibrated microphone (40DP, GRAS).…”
Section: (D) Estimating the Acoustic Detection Range Of The Microphonementioning
confidence: 99%
“…We used miniature on-board microphones, which also include Global Positioning System (GPS), which were fitted on naturally foraging bats. We chose to study Rhinopoma microphyllum bats as these bats are known to be social [16,17], and because they focus their sound energy in a narrow frequency band [18] making them highly prone to be jammed.…”
Section: Introductionmentioning
confidence: 99%